Fibrinogen‐like protein 2 in gastrointestinal stromal tumour. Issue 4 (14th January 2022) - Pulkka, Olli‐Pekka; Viisanen, Leevi; Tynninen, Olli; Laaksonen, Maria; Reichardt, Peter; Reichardt, Annette; Eriksson, Mikael; Hall, Kirsten Sundby; Wardelmann, Eva; Nilsson, Bengt; Sihto, Harri; Joensuu, Heikki
Abstract: Gastrointestinal stromal tumour (GIST), the most common sarcoma of the gastrointestinal tract, can be treated effectively with tyrosine kinase inhibitors, such as imatinib. Cancer immune therapy has limited efficacy, and little is known about the immune suppressive factors in GISTs. Fibrinogen‐like protein 2 (FGL2) is expressed either as a membrane‐associated protein or as a secreted soluble protein that has immune suppressive functions. We found that GISTs expressed FGL2 mRNA highly compared to other types of cancer in a large human cancer transcriptome database. GIST expressed FGL2 frequently also when studied using immunohistochemistry in two large clinical series, where 333 (78%) out of the 425 GISTs were FGL2 positive. The interstitial cells of Cajal, from which GISTs may originate, expressed FGL2. FGL2 expression was associated with small GIST size, low mitotic counts and low tumour‐infiltrating lymphocyte (TIL) counts. Patients whose GIST expressed FGL2 had better recurrence‐free survival than patients whose GIST lacked expression. Imatinib upregulated FGL2 in GIST cell lines, and the patients with FGL2‐negative GIST appeared to benefit most from long duration of adjuvant imatinib. We conclude that GISTs express FGL2 frequently and that FGL2 expression is associated with low TIL counts and favourable survival outcomes.